2015
DOI: 10.4049/jimmunol.1500136
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Sensitization by Death Receptor Fractions of an Anti–Dengue Nonstructural Protein 1 Antibody Induced Plasma Leakage, Coagulopathy, and Mortality in Mice

Abstract: The mechanisms leading to the life-threatening dengue hemorrhagic fever (DHF) remain elusive. DHF preferentially occurs during secondary dengue infections, suggesting that aberrant immune responses are involved in its development. We previously demonstrated that the autoantibodies elicited by dengue virus (DENV) nonstructural protein 1 (NS1; anti–NS1 Igs) induce plasma leakage and mortality in mice with warfarinized anticoagulant suppression. However, the involved pathogenic Ig fractions of anti–NS1 Igs remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 62 publications
0
27
0
Order By: Relevance
“…Recombinant P-sel IgG-Fc fusion protein (rP-sel-Fc) was purchased from R&D Systems (Minneapolis, MN). Using previously described immunization methods54555657, polyclonal anti-P-sel Igs were obtained from rP-sel-Fc immunized rabbits for neutralization analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant P-sel IgG-Fc fusion protein (rP-sel-Fc) was purchased from R&D Systems (Minneapolis, MN). Using previously described immunization methods54555657, polyclonal anti-P-sel Igs were obtained from rP-sel-Fc immunized rabbits for neutralization analysis.…”
Section: Methodsmentioning
confidence: 99%
“…20 Moreover, cross-reaction of anti-NS1 antibodies and direct viral infection of endothelial cells and platelets contribute to hemorrhage, thrombocytopenia and plasma leakage. 22,23 These immune-mediated mechanisms of dengue hemorrhagic fever in peripheral blood have also been found in the brain, where they cause breakdown of the bloodbrain barrier, leukocyte infiltration and local inflammation, followed by vasoconstriction, thromboembolism, cerebral edema, ischemia and hemorrhage. 4,21,24 A few case reports have shown atrial fibrillation as a complication of severe dengue, which may predispose these patients to stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-TACI antibodies were detected in DHF patients and DENV NS1-immunized rabbits. In our previous study, we found anti-TRAIL receptor (DR4; TNFRSF10A) antibody titers in the serum samples of DHF patients and DENV NS1-immunized rabbits 23 . Because death receptor families share structural similarity among members, in this study, we investigated whether antibody fractions against TACI, BCMA, and BAFFR are present in the serum samples of DHF patients and DENV NS1-immunized rabbits.…”
Section: Resultsmentioning
confidence: 90%
“…Clinical [15][16][17] , cellular, and animal studies [18][19][20][21][22][23][24][25][26] have found that DENV infections and DENV nonstructural protein 1 (NS1) immunizations elicit autoantibodies against plasma, platelet, and endothelial antigens. Among these autoantigens, our previous report suggest that endothelial TNF-related apoptosis-inducing ligand (TRAIL) receptor 1 (death receptor 4 [DR4]; also known as TNFRSF10A) could be a potential autoantibody target leading to plasma leakage in severe DENV infections in our previous study 23 . DR4 is a member of the TNF receptor (TNFR) family and shows certain structural similarities with the TNFR family members of TACI, BCMA, and BAFFR.…”
mentioning
confidence: 99%